An update on the treatment of Restless Legs Syndrome/Willis-Ekbom Disease: prospects and challenges. (2nd September 2018) - Zucconi, Marco; Galbiati, Andrea; Rinaldi, Fabrizio; Casoni, Francesca; Ferini-Strambi, Luigi
ABSTRACT: Introduction : Restless Legs Syndrome/Willis-Ekbom Disease (RLS/WED) is a sleep disorder characterized by an urge to move the legs, frequently associated or triggered by unpleasant sensations in the lower limbs that affects approximately 2.5% of adults. Therapy and management of RLS/WED require long-term interventions, since the typical manifestation of this disorder is chronic. Areas covered : In this review, we provide an update regarding the treatment of RLS/WED with particular attention to future challenges for its management. We reviewed a large variety of treatments studied in clinical trials and supported by the most updated guidelines. Alongside with first-line interventions other pharmacological options including opioids, benzodiazepines, iron therapy, and newly studied drugs are discussed. Furthermore, due to the occurrence of augmentation and worsening of symptoms we also reviewed the development of non-pharmacologic alternatives. Expert commentary : The management of RLS/WED is a challenge because of different long-term issues. Several complications, such as loss of the therapeutic effect of dopaminergic or non-dopaminergic agents and augmentation, are still unsolved concerns. However, the development of new drugs acting on adenosinergic and glutamatergic neurotransmission seems promising. Randomized controlled trials are needed in order to recognize effectiveness of new drugs or non-pharmacological treatment strategies.